VD_FINDINFO HC / 2013 / 633 vom 27. September 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, ENFANT, REVENU HYPOTHÉTIQUE | 176 al. 1 ch. 1 CC, 317 al. 1 CPC (CH)